Washable and stretchable fiber with heat and ultraviolet color conversion. Issue 35 (10th August 2022) - Yang, Jonguk; Ju, Sanghyun
Abstract : Thermochromic- and UV-photochromic-materials embedded stretchable fibers showed stable color conversion functionality in response to temperature and UV irradiation even after continuous tensile-shrinkage, exposure to sweat, and detergent exposure. Abstract : Wearable fabric-type color conversion sensors are very effective in quickly expressing danger or warnings to people. In particular, they can visually show information regarding the external environment, such as its temperature or ultraviolet (UV) intensity. However, a wearable sensor worn on the human body should maintain its sensing performance without deterioration even when exposed to various external stimuli, such as the repeated movements caused by human activity, sweat, and washing. In this study, thermochromic and UV photochromic fibers were fabricated to maintain stable color conversion functionality in response to temperature and UV irradiation even after continuous tensile-shrinkage, exposure to sweat and detergent solution. The thermochromic or UV photochromic materials were coated on the inside and outside of strands constituting a highly elastic spandex fiber. By adding polydimethylsiloxane to the color-changing material, the physical and chemical stability of the color-conversion thin film coated on the strand increased. The fabricated thermochromic fiber had a blue-green color and changed to white as the temperature increased, whereas the fabricated UV photochromic fiber was white and changed to purple as the UV intensity increased. In addition, the color conversion coating film was not lost even when exposed to repeated stretching and sweat/washing solutions, and a stable color-change reactivity was maintained. The thermochromic and UV photochromic fibers introduced in this study are expected to contribute to the commercialization of wearable colorimetric sensors by solving the problems regarding the physical stimulation and washing stability of existing coating-type color conversion fibers and textiles.